Cognitive Severity-Specific Neuronal Degenerative Network in Charcoal Burning Suicide-Related Carbon Monoxide Intoxication. Issue 19 (May 2015) - Chen, Nai-Ching; Huang, Chi-Wei; Huang, Shu-Hua; Chang, Wen-Neng; Chang, Ya-Ting; Lui, Chun-Chung; Lin, Pin-Hsuan; Lee, Chen-Chang; Chang, Yen-Hsiang; Chang, Chiung-Chih; Barkin., Robert
<x xml:space="preserve">Abstract</x> Abstract While carbon monoxide (CO) intoxication often triggers multiple intraneuronal immune- or inflammatory-related cascades, it is not known whether the pathological processes within the affected regions evolve equally in the long term. To understand the neurodegenerative networks, we examined 49 patients with a clinical diagnosis of CO intoxication related to charcoal burning suicide at the chronic stage and compared them with 15 age- and sex-matched controls. Reconstructions of degenerative networks were performed using T1 magnetic resonance imaging, diffusion-tensor imaging, and fluorodeoxyglucose positron emission tomography (PET). Tract-specific fractional anisotropy (FA) quantification of 11 association fibers was performed while the clinical significance of the reconstructed structural or functional networks was determined by correlating them with the cognitive parameters. Compared with the controls, the patients had frontotemporal gray matter (GM) atrophy, diffuse white matter (WM) FA decrement, and axial diffusivity (AD) increment. The patients were further stratified into 3 groups based on the cognitive severities. The spatial extents within the frontal-insular-caudate GM as well as the prefrontal WM AD increment regions determined the cognitive severities among 3 groups. Meanwhile, the prefrontal WM FA values and PET signals also correlated significantly with the patient's Mini-Mental State Examination score. Frontal hypometabolic patterns in PET analysis, even after adjusted for GM volume, were highly coherent to the GM atrophic regions, suggesting structural basis of functional alterations. Among the calculated major association bundles, only the anterior thalamic radiation FA values correlated significantly with all chosen cognitive scores. Our findings suggest that fronto-insular-caudate areas represent target degenerative network in CO intoxication. The topography that occurred at a cognitive severity-specific level at the chronic phase suggested the clinical roles of frontal areas. Although changes in FA are also diffusely distributed, different regional changes in AD suggested unequal long-term compensatory capacities among WM bundles. As such, the affected WM regions showing irreversible changes may exert adverse impacts to the interconnected GM structures.